ANTI-PROLIFERATIVE ACTIVITIES OF THE AQUEOUS ROOT EXTRACT OF DIANTHUS THUNBERGII SS HOOPER (CARYOPHYLLACEAE) - Akinrinde, Akinleye; Venter, Maryna Van de; Koekemoer, Trevor; Bradley, Graeme (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: The roots of Dianthus thunbergii SS Hooper are used traditionally in South Africa for the treatment ofdiabetes, wounds, colic, chest complaints and cancer. This study was aimed at investigating the potential anti-proliferativeactivities of the D. thunbergii in mammalian cancer cell lines.Materials and Methods: Aqueous and ethanol extracts of D. thunbergii were tested in vitro on two cancer cell lines:human hepato-cellular carcinoma (HepG2) cells and murine insulinoma (INS-1) cells using the 3-(4,5-Dimethylthiazol-2-yl) 2,5-diphenyltetrazolium bromide (MTT) and crystal violet cell viability assays, as well as live-cell fluorescence imagingmicroscopy. A tentative profiling of the aqueous extract was also carried out using liquid chromatography-massspectrometry (LC-MS).Results: The aqueous extract (50-200μg/ml) exhibited significant (p<0.05) cytotoxicity in HepG2 cells (IC50<50 μg/ml),while also significantly (p<0.05) decreasing the viability of INS-1 cells (IC50=36.0 μg/ml), although no toxicity was evidentin L6 myotubes. Hoechst 33342® and propidium iodide staining of INS-1 cells further revealed significant growthinhibition (p<0.001) of INS-1 cells by the aqueous extract. No meaningful toxicity was, however, obtained with the ethanolextract (IC50 = 204.0 μg/ml). Non-targeted LC-ESI-TOF/MS analysis of the aqueous extract revealed the putative identitiesof main compounds present in the aqueous root extracts, including some that may contribute to its anti-proliferative action.Conclusion: Taken together, the results showed that the roots of D. thunbergii may represent a potential plant-based sourceof agents with anti-proliferative efficacy.